Paradigms in Green Chemistry and Technology - Albini, Angelo; Protti, Stefano (SpringerBriefs in Green Chemistry for Sustainability, 2016)
This brief discusses the formation of modern "green chemistry" as a contribution to sustainability and the historic paths that lead to the key concepts of this discipline. Within this intellectual framework, the book tackles the 12 principles of green chemistry and the 12 principles of green chemical engineering as well as related financial and management issues; these facts are explored and reformulated in a focused set of paradigms. The best choice of a model for quantitative assessment (sufficiently specific to account for the many parameters involved but not excessively detailed to inhibit practical use) is discussed and examples of practical applications are presented.